Pengaruh Tehnik Relaksasi Genggam Jari Terhadap Penurunan Nyeri Pasien Post Operasi Bedah Digestif Di Rumah Sakit Murni Teguh Ciledug - Sari, Afita; Silaen, Harsudianto (Universitas Murni Teguh, 2024)
Pain is a protective mechanism for the body that arises when tissue is damaged and causes the individual to react to relieve pain. Surgery or surgery performed by a doctor using invasive methods of opening or exposing body parts for treatment. Laparotomy is one of the most important surgical procedures where an incision is made in the mucous membrane of the abdominal wall to protect the problematic part of the abdominal organs. Finger grip relaxation is a relaxation technique that is very simple and easy for anyone to do with the fingers and the flow of energy in our bodies. The purpose of this study was to determine theeffect of finger grip relaxation on pain reduction in post-digestive surgery patients. This type of research is pre-experimental one group pre-posttest without control group research design. The population in this study were all post-operative digestive surgery patients at Murni Teguh Hospital in Ciledug. The samples in this study were 20 respondents. The results of the Wilcoxon Signed Rank Test have a significance value (p value = 0.000) where this means that p value <0.05. It is concluded that there is an effect of finger grip relaxation on changes in pain levels in post-digestive surgery patients and it is more effective in reducing pain in post-digestive surgery patients.